Roald Dahl's tales of the unexpected. - Dahl, Roald, 1916-1990. (New York : Vintage Books, 1990)
A collection of short stories that are deliciously nasty, tantalizing, amusing, and sometimes terrifying.
"A Vintage original, September 1979"--T.p. verso.
Young Adult
Keywords: Horror fiction; Short stories